Terranova, l'interpretazione e la filosofia/teoria del diritto - Barberis Mauro (2022)
Giuseppe Terranova, Emeritus of Commercial law at the “La Sapienza” University of Rome, in his book The legal reasoning (2021) addresses important questions of interpretation theory, raising at least three types of reflections. The first one concerns the division of labor, both scientific and academic, between legal dogmatics and philosophy/theory of law. The second reflection concerns Terranova’s own contribution to the theory of interpretation and argumentation, especially by the notions of canonical meaning and application scenario. The third reflection, finally, focuses on the role that philosophy/theory of law could acquire in legal studies, without renouncing the traditional speculative and analytical claims: becoming a ground for meeting/clash among legal dogmatics and non-legal sciences relevant to the jurists.